2011
DOI: 10.1172/jci43242
|View full text |Cite
|
Sign up to set email alerts
|

NKp46 identifies an NKT cell subset susceptible to leukemic transformation in mouse and human

Abstract: IL-15 may have a role in the development of T cell large granular lymphocyte (T-LGL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 61 publications
7
49
1
Order By: Relevance
“…1C). Besides NK cells, discrete subsets of CD4 − CD8 − NK1.1 + T cells also express NKp46 (6,16,17). Consistent with these data, minute percentages of eYPF + αβT and γδT cells were detected in the spleen (Fig.…”
Section: Cd3supporting
confidence: 84%
See 1 more Smart Citation
“…1C). Besides NK cells, discrete subsets of CD4 − CD8 − NK1.1 + T cells also express NKp46 (6,16,17). Consistent with these data, minute percentages of eYPF + αβT and γδT cells were detected in the spleen (Fig.…”
Section: Cd3supporting
confidence: 84%
“…NKp46 is found on all mature NK cells regardless of their anatomic localization in both human and mouse. The selective expression of NKp46 on NK cells has two reported exceptions: rare T-cell subsets (6,16,17) and a mucosal population of NKp46 + innate lymphoid cells (ILCs) that express the transcription factor retinoid-related orphan receptor (ROR)-γt and produce IL-22, a key cytokine for the activation and defense of epithelial cells (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…36 Yu et al demonstrated T-LGL leukemias in IL-15 transgenic mice that expressed NKp46; NKp46-expression was the hallmark of a minute population of wild-type NKT cells with higher activity and potency to become leukemic. 48 Taken together, all these studies showed a role of IL-15 receptor and its signaling pathway in the pathogenesis of LGL leukemia and suggest that these may be useful targets in the treatment of patients with T-LGL or NKT leukemia.…”
mentioning
confidence: 83%
“…Flow cytometric analysis of liver immune cells was performed as described previously (51). The following antibodies reactive with murine cells were obtained from BD: Gr-1 (RB6-8c5), CD11b (M1/70), CD3 (145-2C11), CD19 (1D3), NK1.1 (PK136), IL-6 (MP5-20F3), and TNF-α (MP6-XT22).…”
Section: Generation Of Liver-specific (Lko) and Germline (Ko) Mir122 mentioning
confidence: 99%